The RTRMF-CN clinical experience scheme and students' clinical performance - Apostol, Sarah G. (2000)
This study looked into the effectiveness of the Remedios T. Romualdez Medical Foundation College of Nursing Clinical Experience Scheme (RTRMF-CN) on the third year nursing students' clinical performance. The research problem being worked on is whether the RTRMF-CN Clinical Experience Scheme effects an improved clinical performance. Side by side with this scheme is the role of the students' intelligence quotient level on their clinical performance. This problem formed the basis of the study's objectives and hypotheses.Literature reviewed touch on student learning, faculty factor, teaching strategies and related clinical studies where students and teachers interplay. Culled from various studies, the conceptual framework operates on the clinical scheme plus the students' intelligence quotient level to lead the students to improved clinical performance. Tools such as clinical cases questioning to detect improvement in their clinical care analysis and decisions, nursing care plans and actual clinical performance served as indicators of the quality of clinical performance.Sample were the third year students serving as one group for both the pre and post tests. The research design aptly applied the one group pre and post test model with the RTRMF-CN scheme as the main variable to assess their clinical performance.Findings show that together with other contributory variables such as I.Q. and familiarity of the case, the RTRMF-CN scheme should be fully utilized by the faculty with a common formation and orientation to the tool. The scheme can be beneficial both to the students and faculty in providing quality nurses.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Clinical training